Fishing the Jumps : A Novel - Herrin, Lamar (Book collections on Project MUSE., 2019)
But in fishing the jumps there comes a moment when an insatiable hunger rises up in you and everything turns wild."The term "fishing the jumps" speaks to a method of catching fish while they're in the midst of a wild, frenzied state. And just like the undercurrents that exist in the lakes on which this tale is based, some relationships have a way of hiding -- and revealing -- turmoil just beneath the surface. In his latest novel, award-winning writer Lamar Herrin highlights the art of storytelling and the value of friendship with a lush, outdoor landscape serving as a backdrop. Set over the course of a weekend spent fishing on an Adirondack lake, two middle-aged friends -- Jim McManus and Walter Kidman -- sip Jim Beam on the rocks and share tales of memory and camaraderie as the past and present meld to reveal that what happens in the past rarely stays there. Lyrical and poetic, playful and entertaining, Fishing the Jumps is more than just fishing tales. It is a seamless and haunting novel that is ultimately a story of the deep and necessary relationship between two men and the binding and nourishing effect of family -- not only of an extended family, but of a whole community, and in fact, a whole region